The concept of betrayal in the consciousness of the English: A psycholinguistic study - Mariia Ivanchenko; Iryna Kolegaeva (East European Journal of Psycholinguistics)
The study attempts to reveal verbal, that is, lexically materialised associative responses of English respondents to the word stimulus’ betrayal’. As the word association test is considered a reliable way of studying the content of the national mental image of a specific concept, the method allowed to receive a collective linguistic representation of the researched concept reflected in the consciousness of the tested participants. The association test was held with undergraduate and postgraduate students, respondents with bachelor’s and master’s degrees who were native speakers of English and residents of London (England), aged 18 to 25 (365 males, 411 females). The test results show that the English associate the concept of 'betrayal' with a traitor. They clearly identify the subjects of betrayal – specific persons (historical, public, political figures, heroes of cartoons and literary works) with whom the objects of betrayal were in a close, trusting relationship. The characteristic features of traitors are treachery, lack of empathy, and the desire to hurt deliberately. The motivations behind such persons’ behavioural scenarios are deception, fraud, and searching for personal gain. In the consciousness of English speakers, such behaviour is verbalised as a shameful act, a crime that must be punished. Betrayal causes negative emotions and is characterised as harmful, destructive, and disgusting.